Determinação da eficiência e produtividade de sistemas de produção de bovinos de corte por meio da análise envoltória de dados (DEA) e índice de malmquist - (:unkn) unknown (Universidade Federal do Pampa, 2020)
Analyses that determine the efficiency of rural enterprises and its determining factors are fundamental for strategic purposes in the search for solutions to problems, as well as for planning and decision making. Thus, this work sought to measure the efficiency and productivity of rural properties belonging to a benchmarking group on the western border of Rio Grande do Sul, Brazil. An additional goal was to discriminate the efficient properties from the inefficient ones in the allocation of production factors and to identify determining factors for the efficiency of the studied productive systems. The decision-making units (DMUs) of this study consisted in 11 properties specialized in beef cattle that were submitted to data envelopment analysis and the Malmquist index. The efficiency and productivity of the DMUs were evaluated between 2016 and 2018. The inputs selected through principal component analysis were useful livestock area in hectares, native pasture useful area in hectares, number of field workers, and average herd size in animals. The outputs considered were productivity evaluated as kg of live weight per hectare and revenue in terms of Brazilian reais per hectare. Only 27.2% of the enterprises were considered efficient in each studied year, however, there were advances in total factor productivity. Such advances were determined by technical efficiency due to the correct management of production factors. Although to a lesser extent, there was technological advancement in the group. The analysis of the DMUs showed greater gains in productivity and revenue through reduced use of area and labor and greater intensification of the production system.
Determination of efficiency and productivity of beef cattle production systems through data envelopment analysis (DEA) and malmquist index
Keywords: Ciência animal; Performance analysis; Benchmarking; Rural management; Beef cattle; Análise de desempenho; Benchmarking; Gestão rural; Pecuária de corte; CNPQ::CIENCIAS AGRARIAS